Gewerkschaftssterben in Kolumbien: Über den Zusammenhang von neoliberaler Deregulierung, staatlicher Politik und Paramilitarismus - Zelik, Raul (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2003)
The persecution of labor unionists by paramilitarian groups, the policy of deregulation of the labor market, and the criminalization of labor unions in the public sector seem to pursue the same strategy, Its aim is the weakening or disappearance of organizations that resist a policy which is friendly to (transnational) capital. The 200 murders that are committed every year against Colombian unionists, in that sense, are not only a result of civil war, The article reads the violence in Colombia as an appearance of globalization process.